Flood driving the migration of the prehistoric settlements in the Chengdu plain, southwest China - Daobin Tang; Peng Cui; Weiming Liu; Jiao Wang; Zewen Yang; Zili Wang; Anna Yang; Xiangjun Liu (Quaternary Science Reviews, 2026)

Electron-metal support interactions enhanced by W-O-Zr interface in Pd-UiO-66 catalyst for efficient HDO of lignin derivatives at room temperature - Qunfeng Chen; Daobin Tang; Qi Zhang; Zhiyuan Tang; Longlong Ma; Xinghua Zhang (Chemical Engineering Journal, 2025)

Luminescence dating of cobbles buried in moraines from the source area of the Litang River (Konglongluo Valley), eastern Tibetan Plateau - Kunmei Yang; Xianjiao Ou; Yang Li; Geraint Jenkins; Pan Yao; Daobin Tang; Yantian Xu; Jinming Xie; Lanhua Zeng; Xiangjun Liu (Quaternary Geochronology, 2024)

Heavy metal pollution status and deposition history of mangrove sediments in Zhanjiang Bay, China - Daobin Tang; Songying Luo; Suyan Deng; Rui Huang; Bishan Chen; Ziyi Deng (Frontiers in Marine Science, 2022)
Mangroves have high ecological service value and play an important role in achieving carbon neutrality. However, the ecological services provided by mangroves are gradually declining due to the threat of various pollutants, especially heavy metal (HM) pollution. Researching the status and history of heavy metals (HMs) in mangrove sediments improves understanding of how mangroves can be protected. We studied the Zhanjiang Bay mangroves, which is an important part of the Zhanjiang Mangrove National Nature Reserve, and is greatly affected by human activities, as an example. We analyzed the pollution levels and deposition process of HMs and their influencing factors. In the mangrove surface sediments of Zhanjiang Bay, Pb, Cr, and Co were slightly to moderate enriched and Cu was moderate-heavy enriched. Zn and Hg showed moderate-heavy enrichment and heavy enrichment, respectively. Cu, Zn, Hg, and Co were 1.5, 1.88, 2.66, and 1.27 times the local background, respectively. Cu, Zn, and Hg mainly originated from anthropogenic sources, and Co may have derived from natural sources. The HM data of mangrove sedimentary cores in Zhanjiang Bay were obtained for the first time; high HM content appeared in the deep layer of the cores but not in the mangrove surface sediments. Both cores were well documented for the effects of natural and anthropogenic factors on the deposition process of HMs. Among them, the high enrichment of Hg in 1909–1921 may be closely related to human activities rather than natural formation. Before 1954, dense mangroves favored the accumulation and gradual increase of HMs. The intense human activity in 1945–1963 during the period of economic construction and reclamation of the Nansan Island Engineering led to significant increases in Cu, Zn, Pb, Cr, and Co, which reached their highest values in more than one hundred years. After 1963, anthropic factors such as deforestation and conversion to aquaculture sharply reduced mangrove area. Reclamation engineering enhanced tidal erosion. Natural factors such as precipitation, storm surge, sea-level rise, and high tides have accelerated the erosion and dilution of mangrove sediments in Zhanjiang Bay. These factors have led to the gradual reduction of HM content in sedimentary cores.